Case report: PD-1 inhibitor-based treatment strategies in gastric cancer complicated by bone marrow metastasis and disseminated intravascular coagulation: A report of two cases - Huang, Ren-Ze; Chen, Nuo; Hu, Yan; Hu, Wan-Ming; Wang, Feng-Hua; Chen, Dong-Liang (Frontiers in Oncology, 2023)
Introduction Gastric cancer (GC) complicated by bone marrow metastasis (BMM) and disseminated intravascular coagulation (DIC) represents poor prognosis and most of these patients would die in a few months. Active treatment strategies such as chemotherapy are effective in restoring coagulation function and prolonging patients’ survival time. Immunotherapy including programmed death protein 1 (PD-1) or programmed death protein ligand 1 (PD-L1) inhibitors has emerged as a first-line treatment of gastric cancer. However, the efficacy of PD-1 inhibitor-based treatment strategies in these patients remains unknown. Case description Herein, we presented two cases of advanced gastric cancer (AGC) complicated by BMM and DIC, in which two patients received chemotherapy and PD-1 inhibitor as the first-line treatment. Both of them achieved a partial response after treatment, and the coagulation function was restored. The patient who discontinued the PD-1 inhibitor after 6 months experienced DIC relapse, whereas the other patient who maintained the PD-1 inhibitor treatment cycle remained responsive after 10 months. Conclusions We speculate that PD-1 inhibitor-based treatment strategies are effective and safe in prolonging survival against gastric cancer with BMM and DIC, and the coagulation function is well controlled by the treatment with a combination of immunotherapy and chemotherapy.